Conferring Resistance to Digital Disinformation: The Inoculating Influence of Procedural News Knowledge. Issue 3 (3rd July 2019) - Amazeen, Michelle A.; Bucy, Erik P.
Abstract : Despite the pervasiveness of digital disinformation in society, little is known about the individual characteristics that make some users more susceptible to erroneous information uptake than others, effectively dividing the media audience into prone and resistant groups. This study identifies and tests procedural news knowledge as a consequential civic resource with the capacity to inoculate audiences from disinformation and close this "resistance gap." Engaging the persuasion knowledge model, the study utilizes data from two national surveys to demonstrate that possessing working knowledge of how the news media operate aids in the identification and effects of fabricated news and native advertising.